Pollen and spores as biological recorders of past ultraviolet irradiance - Jardine, Phillip E.; Fraser, Wesley T.; Lomax, Barry H.; Sephton, Mark A.; Shanahan, Timothy M.; Miller, Charlotte S.; Gosling, William D. (Nature Publishing Group, 2016)
Solar ultraviolet (UV) irradiance is a key driver of climatic and biotic change. Ultraviolet irradiance modulates stratospheric warming and ozone production, and influences the biosphere from ecosystem-level processes through to the largest scale patterns of diversification and extinction. Yet our understanding of ultraviolet irradiance is limited because no method has been validated to reconstruct its flux over timescales relevant to climatic or biotic processes. Here, we show that a recently developed proxy for ultraviolet irradiance based on spore and pollen chemistry can be used over long (105 years) timescales. Firstly we demonstrate that spatial variations in spore and pollen chemistry correlate with known latitudinal solar irradiance gradients. Using this relationship we provide a reconstruction of past changes in solar irradiance based on the pollen record from Lake Bosumtwi in Ghana. As anticipated, variations in the chemistry of grass pollen from the Lake Bosumtwi record show a link to multiple orbital precessional cycles (19-21 thousand years). By providing a unique, local proxy for broad spectrum solar irradiance, the chemical analysis of spores and pollen offers unprecedented opportunities to decouple solar variability, climate and vegetation change through geologic time and a new proxy with which to probe the Earth system.